Timing is Everything: Evidence from College Major Decisons - Richard W. Patterson; Nolan G. Pope; Aaron Feudo (Center for Economic Studies and ifo Institute (CESifo), 2019)
People rely on their experiences when making important decisions. In making these decisions, individuals may be significantly influenced by the timing of their experiences. Using administrative data, we study whether the order in which students are assigned courses affects the choice of college major. We use a natural experiment at the United States Military Academy in which students are randomly assigned to certain courses either during or after the semester in which they are required to select their college major. We find that when students are assigned to a course in the same semester as they select a major, they are over 100 percent more likely to choose a major that corresponds to that course. Despite low switching costs, approximately half of the effect persists through graduation. Our results demonstrate that the timing of when students are assigned courses has a large and persistent effect on college major choice. We explore several potential mechanisms for these results and find that students' initial major choice best fits a framework we develop that incorporates salience and availability. Furthermore, our results suggest that once students select a major, they are less likely to switch majors than the standard model of economic choice predicts. Instead, students' decision to remain in a major is more consistent with status quo bias.
Keywords: D03; I23; J24; 330; availability; college major